Popular dissent, human agency, and global politics - Bleiker, Roland (Cambridge studies in international relations, 2000)
Popular dissent, such as street demonstrations and civil disobedience, has become increasingly transnational in nature and scope. As a result, a local act of resistance can acquire almost immediately a much larger, cross-territorial dimension. This book draws upon a broad and innovative range of sources to scrutinise this central but often neglected aspect of global politics. Through case studies that span from Renaissance perceptions of human agency to the collapse of the Berlin Wall, the author examines how the theory and practice of popular dissent has emerged and evolved during the modern period. Dissent, he argues, is more than just transnational. It has become an important 'transversal' phenomenon: an array of diverse political practices which not only cross national boundaries, but also challenge the spatial logic through which these boundaries frame international relations.